Enterprise Architecture Design Vision Architecture and Business Architecture Stage Using TOGAF ADM at SMA ABC - Pamungkas, Ananda Cipta; Samihardjo, Rosalin; Murnawan, Murnawan (Indonesian Scientific Journal, 2025)
Digitalization of Education in realizing the vision of an independent curriculum, encourages the development of educational unit technology. In realizing the development of information technology, enterprise architecture planning (EAP) is used to build a balance between business strategy and information technology in implementing integrated educational unit digitalization. This research was conducted at SMA ABC Bandung. The research method used is The Open Group Framework (TOGAF) Architecture Development Method (ADM) with the aim of explaining and providing a methodology in analyzing EAP and finding the vision architecture and business architecture periodically. The purpose of this study is to design information system management, direct business strategy with planning, information technology governance and educational unit management. Research results In the architectural vision, the research is able to identify the needs of organizational capacity that must be met to support the achievement of the vision and mission of SMA ABC Bandung. While at the Business Architecture stage, it produces a gap analysis (GAP analysis) of existing business processes, produces business process diagrams and functional decomposition diagrams to describe the main and supporting business processes at the school, produces stakeholder identification, organizational scope, and main business processes at SMA ABC, and formulates a catalog of principles that are the basis for the proposed enterprise architecture design.